Representação política e lutas sociais: quem fala em nome de quem no debate sobre a educação de surdos - Regiane Lucas de Oliveira Garcêz (2015)
This dissertation aims at investigating political representation around demands and positions on the discussion about the best education model for deaf people: bilingual, special or inclusive school. Specifically, we seek to understand the place of the affected themselves - organized into a social movement - in the constitution of this representation, compared to other types of political representation. We are interested in the procedural and discursive perspective brought by new approaches to representation, which ultimately connect political issues to the communication perspective. Therefore, we map representative claims in three different settings: a) a closed group of deaf leaders on Facebook; b) a public forum at the Federal Attorney for Citizens' Rights, in December 2011; c) Group Discussion about Education, one of the events of the National Conference of Rights for People with Disabilities in December 2012. The goal was to identify what is represented, who is represented and how the representation is build in discourses about education models for the deaf from the point of view of leaders, managers, legislators and other sources mentioned in this material. We conclude that a) the definition of the represented group, the perception of those affected, the arguments and sources of authority are fluid and depend on the audience; b) the adscritives identities can be used as sources of speech authority for the deaf and people with disabilities, c) the principles and values are the same for representatives from different points of view; d) the representation of social movements in their utterances triggers questions about the very legitimacy in representing, in a meta-representation.